Microporous plugging agent for flexible graphite bipolar plate of ethylene glycol-resistant fuel cell
By using silicone double sealing agent with two (meth)acryloyloxy groups at both ends and a leak plugging agent synthesized by high Tg methacrylate monomer, the dissolution and gas leakage problems of flexible graphite bipolar plates when contacting aqueous ethylene glycol solution at long-term high temperatures are solved, high heat resistance and excellent ethylene glycol resistance are achieved, and the stable operation needs of hydrogen fuel cell vehicles are met.
Patent Information
- Application Number
- CN202411953061.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
When the leak plugging agent of existing flexible graphite bipolar plates comes into contact with the aqueous ethylene glycol solution at long-term high temperature, partial dissolution leads to pore cracks and gas leakage, which cannot meet the requirements of stable operation of hydrogen fuel cell vehicles at long-term high temperatures.
The double sealing agent with two (meth)acryloyloxy groups at both ends and high Tg methacrylate monomers are used as the plugging agents. The double sealing agent is synthesized through hydrogen silicon addition, ring-opening esterification and esterification dehydration reactions to form a plugging agent with high heat resistance and excellent ethylene glycol resistance.
The flexible graphite bipolar plate has achieved resistance to ethylene glycol aqueous solution at long-term high temperatures, avoided dissolution and gas leakage, ensured the airtightness and bending strength of the bipolar plate, and met the stable operation needs of hydrogen fuel cell vehicles.
Smart Images

Figure BDA0005215290650000021 
Figure BDA0005215290650000022 
Figure BDA0005215290650000023
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogen fuel cells, and in particular relates to a thermally cured microporous plugging agent for a flexible graphite bipolar plate of a hydrogen fuel cell stack. Background Art
[0002] Fuel cell bipolar plates are the core structural support components of hydrogen fuel cell stacks, and are divided into metal bipolar plates and graphite bipolar plates. Graphite bipolar plates are widely used in commercial vehicle fuel cell stacks because of their easy availability of raw materials, low cost, good chemical corrosion resistance, and long life. However, the flexible graphite plate itself has a microporous structure and must be impregnated with a plugging agent to ensure the airtightness of the bipolar plate. At the same time, after the plugging agent is cured, the flexible graphite plate must be given sufficient mechanical strength, chemical resistance (mainly ethylene glycol resistance) and long-term heat resistance.
[0003] Flexible graphite bipolar plates generally use (meth) acrylate monomers to compound into impregnated resin liquid as plugging agent (refer to Chinese patent CN 107706430B). Free radical thermal initiator is added before use, and the flexible graphite plate is impregnated in the plugging agent, and vacuum or pressure impregnation is performed to allow the plugging agent molecules to penetrate into the micropores of the flexible graphite bipolar plate, and then the plugging agent remaining on the surface of the bipolar plate is cleaned to prevent the plugging agent from affecting the conductivity of graphite after curing on the surface of the bipolar plate. The bipolar plate is then heated and cured in a water bath, and the plugging agent forms a dense network structure after curing, thereby giving the bipolar plate air tightness, compressive strength, chemical resistance and heat resistance.
[0004] After the flexible graphite bipolar plates are assembled into a fuel cell stack, they will be in contact with an ethylene glycol aqueous solution cooling medium at a temperature of 80 to 95°C for a long time during the operation of the fuel cell. They need to have resistance to the long-term high temperature of the ethylene glycol aqueous solution. (Meth)acrylate polymers have a certain solubility in ethylene glycol. As a result, after the fuel cell has been running for a long time, the bipolar plate plugging agent is partially dissolved in ethylene glycol, resulting in holes and cracks, which lead to gas leakage and failure.
[0005] The Tg of the methacrylate polymer or copolymer mentioned in Chinese patent CN 107706430B is relatively low, and there are few components with a Tg exceeding 100°C. The Tg of the long-chain alkyl acrylate polymer is even lower than zero degrees, and it is in a rubbery state at the operating temperature of the fuel cell. The bending strength of the graphite bipolar plate is greatly reduced, and it is difficult to meet the stringent requirements of hydrogen fuel cell vehicles for stable operation under long-term high temperatures. Summary of the invention
[0006] The purpose of the present invention is to provide a micropore plugging agent for flexible graphite bipolar plates of fuel cells with good heat resistance and ethylene glycol resistance.
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] In a first aspect, the present invention provides a micropore plugging agent for a flexible graphite bipolar plate of an ethylene glycol-resistant fuel cell, comprising: 30 to 50 parts by weight of an organosilicon double-capping agent having two (meth)acryloyloxy groups at both ends and 50 to 70 parts by weight of a high Tg methacrylate monomer, the total of which is 100 parts by weight, as well as 0.5 to 2 parts by weight of a leveling agent and 0.2 to 1.0 parts by weight of a free radical thermal initiator;
[0009] The organosilicon double capping agent having two (meth)acryloyloxy groups at both ends has the following structure:
[0010]
[0011] Wherein, R1 represents a methyl group or a hydrogen atom.
[0012] Preferably, the organosilicon double capping agent having two (meth)acryloyloxy groups at both ends is prepared by the following steps:
[0013] The first step is to use a hydrogen-containing double-capping agent and 4-vinyl cyclohexene oxide to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capping agent containing an epoxy group at each end.
[0014]
[0015] The second step is to conduct a ring-opening esterification reaction between a double-capping agent having an epoxy group at each end and an excess of (meth) acrylic acid in the presence of a ring-opening esterification catalyst to obtain a double-capping agent having a hydroxyl group and a (meth) acryloyloxy group at each end.
[0016]
[0017] The third step is to carry out an esterification dehydration reaction of a double-capping agent having a hydroxyl group and a (meth)acryloyloxy group at each end and an excess of (meth)acrylic acid in the presence of a cyclohexane water-carrying agent and an acidic catalyst to generate a double-capping agent having two acryloyloxy groups at each end.
[0018]
[0019] Wherein, R1 represents a methyl group or a hydrogen atom.
[0020] Specifically, the ring-opening esterification catalyst is selected from tertiary amines and quaternary ammonium salts, and any one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, stannous octoate, tetraethylammonium bromide, etc. is commonly used, and its usage is 0.1% to 5.0% of the reactants.
[0021] Specifically, in order to prevent the (meth)acrylic acid from self-polymerizing during the esterification and dehydration reaction of (meth)acrylic acid, a free radical inhibitor needs to be added during the esterification and dehydration reaction, and the amount added is 0.01% to 1% of the total mass of the reactants.
[0022] More specifically, the free radical inhibitor is any one or two or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone, and 2,6-di-tert-butyl-4-methylphenol.
[0023] Specifically, the acidic catalyst is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, strong acid ion exchange resin and solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, strong acid ion exchange resin and solid super acid, and its added amount is 0.1% to 5.0% of the total mass of the reactants.
[0024] Preferably, the high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuranyl methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, etc. Based on comprehensive considerations such as heat resistance and low viscosity, isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate is preferred.
[0025] Preferably, the leveling agent can be any leveling agent that has a wetting effect on the flexible graphite bipolar plate, and can be determined according to the impregnation amount of the plugging agent after the flexible graphite bipolar plate is wetting. The higher the impregnation amount, the better the effect of the leveling agent. German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants such as CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, CH-9, etc. are preferred.
[0026] Preferably, the free radical thermal initiator is an initiator with a decomposition temperature of 80 to 95° C., and an azo or peroxide free radical thermal initiator is selected. Free radical thermal initiators such as azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide are preferred.
[0027] Preferably, various antioxidants, anti-aging agents, fluorescent agents, etc. may be added to the above composition based on considerations of weather resistance, heat resistance, and fluorescent recognition.
[0028] Compared with the prior art, the advantages of the present invention are:
[0029] (1) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is an organosilicon double-capping agent with two (meth)acryloyloxy groups at each end. Due to the hydrophobic and oleophobic properties and low surface tension of the organosiloxane structure, it has excellent ethylene glycol resistance and will not swell or dissolve when in contact with ethylene glycol aqueous solution under long-term high temperature. It is particularly suitable for plugging micropores in flexible graphite bipolar plates of hydrogen fuel cells.
[0030] (2) One of the components of the flexible graphite bipolar plate plugging agent of the present invention is a silicone double-capping agent compound with two (meth)acryloyloxy groups at each end, each molecule contains 4 (meth)acryloyloxy groups that can be free radical polymerized, and after copolymerization with a high Tg methacrylate monomer, it has high heat resistance, and at the same time, the curing shrinkage rate is relatively low, and the residual stress is small, which is beneficial for the bipolar plate to maintain good bending strength at high temperature. DETAILED DESCRIPTION
[0031] The present invention is described in detail below with reference to the embodiments.
[0032] (Meth)acrylate monomers have the advantages of low viscosity, strong permeability, and low curing temperature. They are the preferred compounds for micropore plugging agents for fuel cell graphite bipolar plates. Compared with acrylate compounds, methacrylate compounds are more susceptible to free radical thermal curing reactions, and the cured products have higher Tg (glass transition temperature), which means they have higher heat resistance. Therefore, most commercial micropore plugging agents use methacrylate monomers as the main component. However, after the polymerization of methacrylate monomers, few have a Tg exceeding 100°C, and their heat resistance is not as good as that of epoxy resin cured products. Also, because the cross-linking density is not high enough and they contain a large number of polar ester bonds, their resistance to ethylene glycol is not good enough.
[0033] The invention introduces a tetrafunctional monomer containing a methylsiloxane structure, which has high Tg and excellent ethylene glycol resistance.
[0034] The organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends of the invention first uses a hydrogen-containing double-capping agent and AGE (allyl glycidyl ether) to undergo a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capping compound with one epoxy group at both ends, and then undergoes an epoxy ring-opening reaction with excess (meth)acrylic acid in the presence of a catalyst. The generated hydroxyl groups are further subjected to an esterification and dehydration reaction with excess (meth)acrylic acid and a cyclohexane water-carrying agent in the presence of an acidic catalyst to generate a double-capping compound with two (meth)acryloyloxy structures at both ends.
[0035] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0036] Synthesis of Epoxy Double-capping Agent
[0037] Into a three-necked glass flask equipped with an oil bath and a condenser, 160 g of 4-vinyl cyclohexene oxide and 0.01 g of chloroplatinic acid were added, the temperature was raised to 70°C with stirring, and 100 g of hydrogen-containing double-capped agent (1,1,3,3-tetramethyldisiloxane) was added dropwise. The addition was completed within one hour, and then the temperature was raised to 80°C and the reaction was continued for 4 hours. The unreacted hydrogen-containing double-capped agent was removed in vacuo to obtain a colorless, transparent double-capped agent containing an epoxy group at each end (referred to as epoxy double-capped agent) with a molecular weight of 382.7.
[0038] Synthesis of Hydroxyacryloxy Double Capping Agent
[0039] Into a three-necked glass flask equipped with an oil bath and a condenser, 100 g of epoxy double-capping agent, 0.5 g of tetraethylammonium bromide, and 0.05 g of MeHQ free radical inhibitor were added. The temperature was raised to 70°C with stirring, and 50 g of acrylic acid was added dropwise within one hour. The temperature was then raised to 80°C and the reaction was continued for 6 hours. Excessive sodium carbonate was added to neutralize the residual acrylic acid and tetraethylammonium bromide. The precipitate was filtered, washed with water several times, and then vacuum dried to obtain a light yellow transparent double-capping agent containing a hydroxyl group and an acryloyloxy group at each end (referred to as hydroxyacryloyloxy double-capping agent) with a molecular weight of 526.8.
[0040] Synthesis of Bisacryloyloxy Double Capping Agent-1
[0041] Add 100g of hydroxyacryloxy double-capping agent, 0.05g of MeHQ free radical inhibitor, 0.05g of BHT free radical inhibitor, 0.5g of trifluoromethanesulfonic acid, and 100g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and a condenser device, stir and heat to 85°C and reflux, add 35g of acrylic acid dropwise, and complete the addition within one hour. The water brought out is regularly released with a separatory tube, and the amount of water retained in the separatory tube is carefully observed until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual acrylic acid and trifluoromethanesulfonic acid, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two acryloyloxy groups at each end (referred to as bisacryloxy double-capping agent-1), with a viscosity of 387mPas and a molecular weight of 634.9.
[0042] Synthesis of Hydroxymethacryloyloxy Double Capping Agent
[0043] Add 100g of epoxy double-capping agent, 0.5g of tetraethylammonium bromide, and 0.05g of MeHQ free radical inhibitor into a three-necked glass flask equipped with an oil bath and a condenser tube, stir and heat to 70°C, add 60g of methacrylic acid dropwise, and complete the addition within one hour, then heat to 80°C and continue the reaction for 6h, add excess sodium carbonate to neutralize the residual methacrylic acid and tetraethylammonium bromide, filter the precipitate, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with one hydroxyl group and one methacryloyloxy group at each end (referred to as hydroxymethacryloyloxy double-capping agent), with a molecular weight of 554.8. Synthesis of dimethacryloyloxy double-capping agent-2
[0044] Add 100g of hydroxymethacryloyloxy double-capping agent, 0.05g of MeHQ free radical inhibitor, 0.05g of BHT free radical inhibitor, 0.5g of trifluoromethanesulfonic acid, and 150g of cyclohexane water-carrying agent into a three-necked glass flask with an oil bath and a condenser, stir and heat to 85°C and reflux, add 42g of methacrylic acid dropwise, and complete the addition within one hour. The water brought out is regularly released with a separatory tube, and the amount of water retained in the separatory tube is carefully observed until no more excess water is distilled out, and the reaction is considered complete. Cool to room temperature, add excess sodium carbonate to neutralize the residual acrylic acid and trifluoromethanesulfonic acid, precipitate and filter, wash with water several times, and then vacuum dry to obtain a light yellow transparent double-capping agent with two methacryloyloxy groups at each end (referred to as double methacryloyloxy double-capping agent-2), with a viscosity of 412mPas and a molecular weight of 690.9.
[0045] The plugging agent formulations in the embodiments and comparative examples are prepared by mixing the various components and stirring them evenly until the solid substances are dissolved into a transparent liquid.
[0046] The formulations of the embodiments and comparative examples are shown in Table 1 below.
[0047] Table 1
[0048] Example-1 Example-2 Example-3 Example-4 Example-5 Comparative Example-1 Comparative Example-2 Comparative Example-3 Bisacryloxy double capping agent-1 30 45 35 10 Bis(methacryloyloxy) double capping agent-2 40 35 Isobornyl acrylate 70 90 Isobornyl Methacrylate 60 55 50 50 Dicyclopentadiene acrylate 65 Tricyclodecyl methacrylate 65 50 Dipropylene glycol diacrylate 50 Azobisisobutyronitrile thermal initiator 0.5 0.5 0.5 0.5 0.5 Benzoyl peroxide thermal initiator 0.5 0.5 0.5 BYK-333 leveling agent 1.0 1.0 1.0 1.0 1.0 1.0 BYK-3505 leveling agent 1.0 1.0 Tg (DMA, tanδ peak)℃ 125 174 149 171 182 106 166 89 Ethylene glycol resistance ○ ◎ ◎ ◎ ◎ △ × ×
[0049] The evaluation method for ethylene glycol resistance is as follows:
[0050] Pour 10g of the plugging agent into a Teflon mold with a diameter of 4.0cm and a height of 2.0cm, heat it in an 80℃ drying oven for 2h, then heat it to 120℃ and continue heating it for 2h to obtain a colorless and transparent cylindrical solid. Put the cylindrical solid into a glass bottle with 50%wt ethylene glycol aqueous solution and seal it, move it into a 90℃ oven and keep it for 1000h, take it out to examine the solubility of the solid and the turbidity of the ethylene glycol aqueous solution, so as to evaluate the ethylene glycol resistance of the plugging agent.
[0051] Ethylene glycol resistance is divided into 4 levels:
[0052] 1. Excellent◎ (the solidified material is intact, the ethylene glycol aqueous solution is transparent and free of foreign matter and turbidity)
[0053] 2. Good (no obvious dissolution of the solidified material, and the ethylene glycol aqueous solution is slightly turbid)
[0054] 3. General △ (the solidified material is obviously dissolved, and the ethylene glycol aqueous solution becomes turbid)
[0055] 4. Very poor × (the solidified material swells and dissolves, and the ethylene glycol aqueous solution is slightly very turbid).
[0056] According to Table 1, by comparing Example 1 and Comparative Example 1, it is found that the amount of bisacryloxy double capping agent added has a crucial influence on the ethylene glycol resistance. The bisacryloxy double capping agent added in an amount exceeding 30 phr (parts per hundred) can achieve better resistance. When the bisacryloxy double capping agent added in an amount of 10 phr, the solidified material is obviously dissolved after aging, and the ethylene glycol aqueous solution becomes turbid. At the same time, the Tg of the obtained solidified material is relatively low, and the heat resistance is also poor.
[0057] The composition of Comparative Example 2 is all high-Tg methacrylate, and the Tg of the cured product is relatively high. However, because it does not contain an organic siloxane structure, its resistance to ethylene glycol is relatively poor. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is slightly turbid.
[0058] The formula of Comparative Example 3 contains low-Tg difunctional acrylate, and the resulting cured product has a relatively low Tg, poor heat resistance, and relatively poor ethylene glycol resistance. After aging, the cured product swells and dissolves, and the ethylene glycol aqueous solution is also very turbid.
Claims
1. A micropore plugging agent for ethylene glycol-resistant flexible graphite bipolar plates of fuel cells, characterized in that: include: 30-50 parts by weight of an organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends and 50-70 parts by weight of a high Tg methacrylate monomer, the total of which is 100 parts by weight, as well as 0.5-2 parts by weight of a leveling agent and 0.2-1.0 parts by weight of a free radical thermal initiator; The organosilicon double-capping agent with two (meth)acryloyloxy groups at both ends has the following structure: Wherein, R1 represents a methyl group or a hydrogen atom.
2. The plugging agent according to claim 1, characterized in that: The organosilicon double capping agent with two (meth)acryloyloxy groups at both ends is prepared by the following steps: The first step is to use a hydrogen-containing double-capping agent and 4-vinyl cyclohexene oxide to carry out a hydrosilylation reaction in the presence of a platinum catalyst to generate a double-capping agent containing an epoxy group at each end. The second step is to conduct a ring-opening esterification reaction between a double-capping agent having an epoxy group at each end and an excess of (meth) acrylic acid in the presence of a ring-opening esterification catalyst to obtain a double-capping agent having a (meth) acryloyloxy group and a hydroxyl group at each end. Wherein, R1 represents a methyl group or a hydrogen atom; The third step is to carry out an esterification dehydration reaction of a double-capping agent having a (meth)acryloyloxy group and a hydroxyl group at each end and excess (meth)acrylic acid in the presence of a cyclohexane water-carrying agent and an acidic catalyst to generate a double-capping agent having two (meth)acryloyloxy groups at each end.
3. The plugging agent according to claim 2, characterized in that: A free radical inhibitor is added in the esterification dehydration reaction, and the amount of the free radical inhibitor added is 0.01% to 1% of the total mass of the reactants.
4. The plugging agent according to claim 3, characterized in that: The free radical inhibitor is any one or more of p-methoxyphenol, hydroquinone, 2,5-dimethylhydroquinone and 2,6-di-tert-butyl-4-methylphenol.
5. The plugging agent according to claim 2, characterized in that: The ring-opening esterification catalyst is selected from tertiary amines and quaternary ammonium salts, and is commonly used any one of triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, trimethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, chromium isooctanoate, stannous octoate, and tetraethylammonium bromide, and its usage is 0.1% to 5.0% of the reactants.
6. The plugging agent according to claim 2, characterized in that: The acidic catalyst is selected from any one of concentrated sulfuric acid, sodium bisulfate, methanesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, preferably any one of methanesulfonic acid, trifluoromethanesulfonic acid, strongly acidic ion exchange resin and solid super acid, and its addition amount is 0.1% to 5.0% of the total mass of the reactants.
7. The plugging agent according to claim 1, characterized in that: The high Tg methacrylate monomer is selected from any one of isobornyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, benzyl (meth)acrylate, phenyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, tetrahydrofuran methacrylate, tricyclodecyl (meth)acrylate, dicyclopentadiene (meth)acrylate, (meth)acryloylmorpholine and N,N-dimethylacrylamide, preferably isobornyl (meth)acrylate, dicyclopentadiene (meth)acrylate or tricyclodecyl methacrylate.
8. The plugging agent according to claim 1, characterized in that: The leveling agent is selected from any one of German BYK leveling agents BYK-333 and BYK-3505, and three positive polymer superdispersants CH-1, CH-2, CH-3, CH-5, CH-6, CH-7, CH-8, and CH-9.
9. The plugging agent according to claim 1, characterized in that: The free radical thermal initiator is an azo or peroxide free radical thermal initiator with a decomposition temperature of 80 to 95° C., preferably any one of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
10. The plugging agent according to claim 1, characterized in that: The plugging agent also includes one or more of an antioxidant, an anti-aging agent, and a fluorescent agent.
Citation Information
Patent Citations
A microporous filler for a bipolar graphite plate for a hydrogen fuel cell
CN107706430B
Hydrolysis-resistant sealant for proton membrane of fuel cell and sealing membrane
CN112877027A
UV (ultraviolet) adhesive for difficult-to-adhere materials
CN119081641A
Optical semiconductor sealing silicone resin composition
JP2010248446A
Radical-curable seal member for fuel cell
US20210313596A1